Isolation and characterization of a recombinant lambda gt11 bacteriophage which expresses an immunoreactive Mycobacterium intracellulare protein in Escherichia coli. - Morris, S L (1988)
Disseminated Mycobacterium avium-Mycobacterium intracellulare (M. avium complex) disease is a prevalent opportunistic infection in patients with acquired immune deficiency syndrome. Because of the increasing importance of this disease, an M. avium complex lambda gt11 expression library was prepared. We screened the library with an absorbed anti-M. intracellulare serum and identified a recombinant phage which expressed a 190-kilodalton beta-galactosidase-M. intracellulare fusion protein. Lysates containing the 190-kilodalton fusion protein evoked strong humoral and cell-mediated responses. The immunoreactivity of the M. intracellulare recombinant protein suggests that antigens isolated from the expression library may be useful as skin test, serodiagnostic, or immunoprophylactic reagents for M. avium complex disease.